Assessment of Total Procollagen Type 1 Intact N-terminal Propeptide, C-telopeptide of type 1 collagen, Bone Mineral Density and its Relationship to Body Mass Index in Men with Type 2 Diabetes - ABED, ELAF; Dr Manal K Rasheed,; Dr Khalaf G.Hussein , (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Type 2 diabetes negatively affects the biochemical parameters of bone turnover more than obesity and is associated with an increased risk of osteoporosis and fragility fractures. Obesity and type 2 diabetes (T2DM) are linked to increased fracturing risk; however, the effect of obesity on diabetes-related bone deficit is unknown.Objective: The goal of this research is to compare the indications, bone density, and bone turnover in T2DM men and a control group, and to investigate the effect of body mass index on bone turnover levels.Subjects, Material and Method: This case-control study was conducted on 120 men whose ages were from 40 - 69 years. They were grouped into two categories: T2DM (n=80) and healthy control (n=40). Serum samples from both groups were analyzed for blood glucose, Calcium and Albumin, by using (Cobas c111), PTH by (Cobas e 411), P1NP and CTX-1 levels in the serum using ELISA kits. Participants underwent (DEXA) measuring Bone Mass Density (BMD) at the lumbar spine.Results: The control (obese and non-obese) participants had statistically significant higher levels of CTX-1 and P1NP than the patients (obese and non-obese) (P-value = 0.000). There was no significant differences in Spine BMD, T-score (p-value = 0.27 and 0.37 respectively).Conclusion: Men with T2DM had a low bone turnover level and deteriorated bone quality compared to controls. The obese healthy controls can maintain healthy bone metabolism if T2DM is prevented.